2016
DOI: 10.1007/s00406-016-0750-1
|View full text |Cite
|
Sign up to set email alerts
|

Repression of telomere-associated genes by microglia activation in neuropsychiatric disease

Abstract: Microglia senescence may promote neuropsychiatric disease. This prompted us to examine the relationship between microglia activation states and telomere biology. A panel of candidate genes associated with telomere maintenance, mitochondrial biogenesis, and cell-cycle regulation were investigated in M1- and M2-polarized microglia in vitro as well as in MACS-purified CD11b+ microglia/brain macrophages from models of stroke, Alzheimer’s disease, and chronic stress. M1 polarization, ischemia, and Alzheimer patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…Human microglia are exposed to decades of metabolic stress brought about by a multitude of factors, with continuous cycles of mitosis that promote replicative senescence. In vitro studies have shown that rat and human microglia undergo senescence by progressive telomere shortening [ 31 , 32 ]. Therefore, the deterioration of microglia could be crucial for the development of aging-related neurodegenerative disease.…”
Section: Microglia In the Aged Cnsmentioning
confidence: 99%
“…Human microglia are exposed to decades of metabolic stress brought about by a multitude of factors, with continuous cycles of mitosis that promote replicative senescence. In vitro studies have shown that rat and human microglia undergo senescence by progressive telomere shortening [ 31 , 32 ]. Therefore, the deterioration of microglia could be crucial for the development of aging-related neurodegenerative disease.…”
Section: Microglia In the Aged Cnsmentioning
confidence: 99%
“…Post-mortem research shows a significant reduction in telomere length across brain regions, especially in the hippocampus, of patients with MDD (Mamdani et al, 2016 ). Repression of telomere-associated genes leads to microglial senescence, a mechanism of neuropsychiatric diseases (Kronenberg et al, 2017 ).…”
Section: Telomerase and Diseases In The Central Nervous Systemmentioning
confidence: 99%
“…Magnetic-activated cell separation (MACS) has been used to isolate microglia and monocyte-derived macrophages (MMϕ) in mouse models of Alzheimer’s disease (Kronenberg et al, 2017), glioma (Szulzewsky et al, 2015), ischemic stroke (Yang B. et al, 2016), and ICH (Lan et al, 2017a). However, to our knowledge, no protocol exists for separating the two cell types after ICH.…”
Section: Introductionmentioning
confidence: 99%